(untitled) (Agora for Physical Education and Sport, 2020)
Soccer can be an excellent moral school or, on the contrary, a proclivity environment for undesirable learning derived from discriminatory acts, not exemplary behaviors and unpleasant feelings and experiences. Referees are one of the backbones of sport, and one of the agents that most perceives and experiences conflict situations. The aim of this work is to know the thoughts of a group of referees about the educational component attributed to grassroots football and about their possible role as educators. To this end, semi-structured interviews were conducted with eight referees, men and women, of various ages, nationalities and categories of the Technical Committee of Referees of the Valencian Autonomous Federation, an entity that was asked for permission to contact the participants. An inductive analysis of the transcripts was performed to make sense of the collected data. The referees interviewed refer to positive and negative aspects in grassroots football, but emphasize the role of the latter. They consider that grassroots football has limited possibilities of becoming an educational context. This opinion is supported by the unpleasant comments they hear from viewers, the excessive pressure they notice from adults towards infants, invitations to violence from viewers, and even some fights between parents. The referees consider that due to the lack of effective time, their pedagogical work is limited to the teaching of the regulations, with the responsibility of social and moral education falling mainly on parents and coaches.